2007
DOI: 10.1007/s00345-007-0220-5
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes related to activation or detoxification of carcinogens might interact with smoking to increase renal cancer risk: results from The Netherlands Cohort Study on diet and cancer

Abstract: Metabolic gene polymorphisms have previously been suggested as risk factors for renal cell carcinoma (RCC). These polymorphisms are involved in activation or detoxiWcation of carcinogens in cigarette smoke which is another RCC risk factor. We evaluated gene-environment interactions between CYP1A1, GST 1 and smoking in a large population-based RCC case group. The Netherlands Cohort Study on diet and cancer (NLCS) comprises 120,852 persons who completed a questionnaire on smoking and other risk factors at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…There is the possibility that ADH7 (rs1154454) may have a direct influence on the association between alcohol intake and RCC risk, or may be in high linkage disequilibrium with the variant responsible for the effect modification . We are not aware of any published report on gene–alcohol interaction in RCC, although interaction between gene variants and other risk factors of RCC (e.g., smoking, hypertension, vitamin D status and meat‐related carcinogens) have been reported . Because the observed gene–alcohol interaction is novel, additional studies are needed to validate the findings and evaluate interaction with a wider spectrum of SNPs in alcohol metabolizing genes.…”
Section: Discussionmentioning
confidence: 99%
“…There is the possibility that ADH7 (rs1154454) may have a direct influence on the association between alcohol intake and RCC risk, or may be in high linkage disequilibrium with the variant responsible for the effect modification . We are not aware of any published report on gene–alcohol interaction in RCC, although interaction between gene variants and other risk factors of RCC (e.g., smoking, hypertension, vitamin D status and meat‐related carcinogens) have been reported . Because the observed gene–alcohol interaction is novel, additional studies are needed to validate the findings and evaluate interaction with a wider spectrum of SNPs in alcohol metabolizing genes.…”
Section: Discussionmentioning
confidence: 99%
“…CpG dinucleotides are commonly mutated in genetic diseases [Kinzler and Vogelstein, 1996] and are often the result of methylation or spontaneously deamination of cytosine and 5-methylcytosine becoming uracil or thymine (thus causing G:C to A:T transition), respectively [Duncan and Miller, 1980]. Methylation of the VHL promoter is a common mechanism of inactivation (8-11%) in sporadic RCC [Herman et al, 1994;Nickerson et al, 2008;Smits et al, 2008]. Dinucleotide CpG hotspot mutations were found in both Japanese and Caucasian patients; however, the incidence was lower in Japanese patients [Yoshida et al, 2000].…”
Section: Ethnic Diversitymentioning
confidence: 99%
“…Within this family of genes, GSTM1 and GSTT1 are most frequently studied in relation to renal cell cancer, and are active in the detoxification of polycyclic aromatic hydrocarbons in tobacco smoke and halogenated solvents. Studies of the main effects of GSTM1 and GSTT1 have not produced consistent association with renal cell cancer,157–162 although the largest study with 925 cases and 1247 control subjects found no association 160. When examined with environmental exposures, several studies reported differences in risk in subgroups defined by genotype status.…”
Section: Genetic Susceptibility and Environmentmentioning
confidence: 99%
“…Polymorphisms in genes encoding other Phase I (activation) and Phase II (detoxification) metabolic enzymes and their interaction with environmental exposures on renal cell cancer risk have also been examined, including GSTP1 , NAT2 , CYP1A1 , CYP1B1 , CYP2E1 , CYP2D6 , and NQ01 157,158,160162,165167. Of the few studies that have examined GSTP1, no main effect of the gene was observed, but some suggested interactions with other genes to influence cancer risk 157,158,160,161.…”
Section: Genetic Susceptibility and Environmentmentioning
confidence: 99%